Peer contagion effect on the academic behaviour of year 9 students at SMPN 1 Pekalongan - Trendi Yudha Purnama; Hendri Ardianto; Komang Sutawan (International Journal of Science and Applied Science: Conference Series, 2025)
Social interaction in education, especially among peers, plays an important role in shaping students' academic behaviour. One interesting phenomenon in educational psychology studies is the peer contagion effect, which is the tendency of individuals to imitate or adjust their behaviour to their peer group, both positively and negatively. This effect is particularly influential during adolescence, when self-discovery and social pressure are dominant factors in shaping behaviour, including in an academic context. This study aims to determine the influence of peer contagion effects on the academic behaviour of Year 9 students at SMP Negeri 1 Pekalongan in the 2024/2025 academic year. The phenomena observed include the use of foul language, difficulty concentrating on studying due to peer influence, and the emergence of stress and depression in the learning process. From a Buddhist perspective, ethical behaviour such as sammā-vācā (right speech) and sammā-kammanta (right action) are important foundations in character building and learning discipline. The results of this study are expected to contribute theoretically to the development of educational science and provide practical benefits for teachers, students, parents, and educational institutions in overcoming the negative effects of peer influence. This study also highlights the importance of strengthening moral and ethical values through Buddhist-based character education as a preventive measure against deviant behaviour in the school environment. By integrating ethical values into the curriculum, it is hoped that students will be better able to cope with peer pressure and develop positive academic behaviour. In addition, this approach can also create a more supportive learning environment where students can be inspired to achieve better results.